2021
DOI: 10.1177/17588359211033704
|View full text |Cite
|
Sign up to set email alerts
|

CirculatingTP53mutations are associated with early tumor progression and poor survival in pancreatic cancer patients treated with FOLFIRINOX

Abstract: Background: Biomarkers predicting treatment response may be used to stratify pancreatic ductal adenocarcinoma (PDAC) patients for therapy. The aim of this study was to identify circulating tumor DNA (ctDNA) mutations that associate with tumor progression during FOLFIRINOX chemotherapy, and overall survival (OS). Methods: Circulating cell-free DNA was analyzed with a 57 gene next-generation sequencing panel using plasma samples of 48 PDAC patients of all disease stages. Patients received FOLFIRINOX as initial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…We found that, the correlation coefficient r and the κ value for the concordance between mutations of the 5 most frequently mutated genes in matched tumor and blood samples ranged from 0.49 to 0.93 and from 0.48 to 0.76, respectively, which is in line with previous studies [ 41 , 64 ]. This suggests that mutations in ctDNA could well reflect and serve as surrogate for the mutations in the deriving tumor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that, the correlation coefficient r and the κ value for the concordance between mutations of the 5 most frequently mutated genes in matched tumor and blood samples ranged from 0.49 to 0.93 and from 0.48 to 0.76, respectively, which is in line with previous studies [ 41 , 64 ]. This suggests that mutations in ctDNA could well reflect and serve as surrogate for the mutations in the deriving tumor.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that in patients with mPDAC TP53 mutations in ctDNA at initial diagnosis and the third measurement but not in tumor predicted shorter OS, both in univariable and multivariable analyses, which is in line with a previous study [ 63 ]. TP53 -mutated ctDNA at baseline predicted early tumor progression in patients with PDAC receiving FOLFIRINOX chemotherapy [ 64 ]. Through both univariable and multivariable analyses, we also revealed that high CDKN2A and SMAD4 mutation abundances in ctDNA but not in tumor and high ARID1A mutation abundances in both ctDNA and tumor at baseline and/or the second measurement were linked to inferior OS and/or PFS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis, early diagnosis and precise treatment remain challenging. Studies have revealed that TP53 mutation occurred in approximately 70% of patients with PAAD and was one of the major factors involved in development and progression of PAAD [ 28 – 31 ]. In this study, CENPL was rarely mutated in PAAD.…”
Section: Discussionmentioning
confidence: 99%